Options for wastewater management in Harare, Zimbabwe - Nhapi, Innocent (A.A. Balkema Publishers, 2004)
"The sustainable management of waste water should aim at pollution prevention and reduction first, followed by resource recovery and reuse. This work shows that substantial water quality improvements could be achieved through a so-called 3-Step Stategic Approach. The frameworks developed in this research for managing water on-site and at centralized and de-centralized levels can be used in re-designing current systems or designing new systems thatmake optimal use of wastewater components whilst minimising pollution."--Provided by publisher.